Evaluation of the quality of information available on the internet on vaginal meshes - Furtado Meinberg, Mariana; Cardoso Brandão, Wladmir; Andrade Werneck, Rogéria; Zarnowski Passos, Michael [UNESP]; da Silva-Filho, Agnaldo Lopes (Elsevier, 2021)
Objective: The objective of this study was to evaluate the quality of information on the internet about vaginal meshes available to the general population. Study design: The terms “vaginal sling,” “sling vagina,” “vaginal mesh,” “mesh vagina,” “vaginal tape,” and “tape vagina” were used every time on three major search engines, and the first 10 websites retrieved by each search engine were selected and evaluated using the DISCERN questionnaire. The websites were divided into four categories based on the type of agency that created the website. These included websites created by private health institutions, non-private health institutions, and non-health institutions and websites for encyclopedias, libraries, articles and scientific papers. They were compared in terms of the reliability, information quality, and total DISCERN score. Results: The survey yielded 98 different websites; after applying the exclusion criteria, 62 sites were selected. Websites for articles, magazines, libraries, and encyclopedias and those by non-private health services had significantly high scores for the reliability dimension of the DISCERN tool as compared to the other two website categories (p < 0.05). Regarding the quality of information, websites for non-specific health services and those for articles, magazines, libraries, and encyclopedias presented significantly lower scores as compared to the other two website categories. Websites for non-specific health services had significantly lower average total DISCERN points when compared to other website categories. The websites for private health services and those for articles, magazines, libraries, and encyclopedias had significantly lower DISCERN scores than the websites for non-private health services did. Conclusion: Our findings showed that the quality of information regarding vaginal meshes on the first 10 websites on major search engines was moderate.
Keywords: Evaluation; Internet; Quality of information; Vaginal mesh